COMPARING BOOK CENSORSHIP: AN ITALIAN AND EUROPEAN PERSPECTIVE (CENTURIES XVI-XVIII) - Sabato, Milena (European Scientific Journal, ESJ, 2014)
This article deals with the theme of book censorship between the 16th and 18th centuries, a complex phenomenon whose equal participants were the Church and the States, with the latter interested in controlling ideas with a view to an absolutistic consolidation of their domains, and thus often in conflict with the centralised control promoted by the religious authority at a European level. Revisiting the various forms of censorship, their evolution and their cultural and civil consequences, the situations of the various European national areas are analysed and compared, thus outlining their characteristics.